Effect of Work Supervision and Discipline on Employee Performance: Study on A Manufacturing Company in Bandung City - Kiki Andang P; Aan Hardiyana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This study aimed to determine the effect of supervision and work discipline on employee performance. This research method uses a quantitative approach with multiple regression analysis. The source of this research uses primary data. This research data collection using a questionnaire. The sample of this research is 57 employees using the saturated sampling technique. The results of this study indicate that partially and simultaneously, there is a significant influence between the variables of supervision and work discipline on employee performance, where supervision and work discipline have a simultaneous effect of 58.8% on employee performance. At the same time, the remaining 41.2% were influenced by other factors not observed in this study. Recommendations for performance the supervision carried out can be hiring human resources following the qualifications. Furthermore, preferably implementing a reward and punishment system for those who have a good or inadequate level of work discipline, pay attention to the level of employee attendance, establish rules, and strict legal sanctions.